The Effect of Warm Compress Therapy on Reducing Gastritis Pain: A Literature Review - Saputri, Dewi Anggi; Sari, Putri Irwanti; Nasution, Riska Amalya; Meinarisa (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Gastritis is an inflammation of the gastric mucosa caused by irritation and infection factors from increased stomach acid. One way to treat gastritis is with non-pharmacological therapy, namely warm compresses. Giving warm compresses is an action to stimulate the skin and tissue to reduce pain, increase comfort and get other therapeutic effects through exposure to heat. The purpose of this case study was to determine the effect of warm compresses on acute pain in gastritis patients. This research method uses a systematic literature review method, searching with an electronic database. The inclusion criteria used were articles with gastritis patients who experienced mild, moderate, severe pain that could be accessed in full text and the research was described in the PICOT analysis. The journal years used were limited to 2019-2024. The results based on a literature review of 7 journals found a decrease in pain in respondents after warm compresses were given. Warm compresses can reduce muscle spasms and provide comfort to patients. It can be concluded that giving warm compresses has an effect on reducing pain in gastritis patients.